Defined Antigen Skin Test for Bovine Tuberculosis Retains Specificity on Revaccination With Bacillus Calmette–Guérin - Subramanian, Saraswathi; Srinivasan, Sreenidhi; Ramaiyan Selvaraju, Kathiravan; Vinoli, Priyadharshini Michael; Selladurai, Suganya; Ramasamy, Boominathan; Kumaragurubaran, Karthik; Bakker, Douwe; Vordermeier, Martin; Kapur, Vivek; Gopal, Dhinakar Raj (Frontiers in Veterinary Science, 2022)
Bacillus Calmette-Guérin (BCG) vaccination provides partial protection against and reduces severity of pathological lesions associated with bovine tuberculosis (bTB) in cattle. Accumulating evidence also suggests that revaccination with BCG may be needed to enhance duration of immune protection. Since BCG vaccines cross-react with traditional tuberculin-based diagnostic tests, a peptide-based defined antigen skin test (DST) comprising of ESAT-6, CFP-10 and Rv3615c to detect infected among BCG-vaccinated animals (DIVA) was recently described. The DST reliably identifies bTB infected animals in experimental challenge models and in natural infection settings and differentiated these from animals immunized with a single dose of BCG in both skin tests and the interferon-gamma release assay (IGRA). The current investigation sought to assess the diagnostic specificity of DST in calves (Bos taurus ssp. taurus x B. t. ssp. indicus; n = 15) revaccinated with BCG six-months after primary immunization. The results show that none of the 15 BCG-revaccinated calves exhibited a delayed hypersensitivity response when skin-tested with DST 61-days post revaccination, suggesting 100% assay specificity (one- tailed lower 95% CI: 82). In contrast, 8 of 15 (diagnostic specificity = 47%; 95% CI: 21, 73) BCG- revaccinated calves were positive when administered the single cervical tuberculin (SCT) test using bovine tuberculin. Together, these results show that the DST retains its specificity even after revaccination with BCG and confirms the potential for implementation of BCG-based interventions in settings where test- and-slaughter are not economically or culturally feasible.